DETERMINATION OF POWER LOSSES FROM TRANSIT FLOW IN ELECTRIC NETWORKS - Burykin, Alexander; Vydmysh, Vladimir; Medianyj, Pavel (Scientific Works of Vinnytsia National Technical University, 2015)
The paper proposes a procedure for determination of power losses from transit flows in the electric system .networks. The procedure is based on the superposition method. Calculations are performed on the basis of current distribution for the linear model of the normal mode of the electric system operation, which is fully equivalent to the initial non-linear model for a given moment of time.